Meningkatkan Kemampuan Perilaku Prososial Melalui Permainan Ular Naga Pada Anak Usia Dini 5-6 Tahun - Ela Pebriani; Nina Hesni (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The purpose of this study was to find out whether playing the dragon snake can improve prosocial behavior skills in children aged 5-6 years in the MELATI PAUD Unit, Gunung Egypt Village, Semidang Alas Maras District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were 15 children aged 5-6 years. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing the ability of prosocial behavior through playing dragon snake in the PAUD MELATI Unit, Seluma Regency, in the first cycle of the first meeting was 69% and in the second cycle of the first meeting there was an increase of 96%. The conclusion of the study that playing the dragon snake can improve the ability of prosocial behavior in children in the Seluma Regency Early Childhood Education Unit, it is proven that in cycle II there was a significant increase, the percentage of achievement was 96% with very good development criteria (BSB).